The 2016 World Health Organization classification of tumours of the central nervous system: what the paediatric neuroradiologist needs to know - Chhabda, Sahil; Carney, Olivia; D’Arco, Felice; Jacques, Thomas S.; Mankad, Kshitij (Quantitative Imaging in Medicine and Surgery; Vol 6, No 5 (October 31, 2016): Quantitative Imaging in Medicine and Surgery (Pediatric Neuro-radiology: Clinical Topics and Technical Development), 2016)
The recently published 2016 World Health Organization (WHO) classification of tumours of the Central Nervous System (CNS) introduces a number of significant changes from the previous edition. Based on an improved understanding of the genetic and molecular basis of tumorigenesis there has been a shift towards defining tumours by means of these characteristics in addition to their histological features, thus providing an integrated diagnosis. In this article, we will provide a concise overview of the salient changes in the 2016 WHO classification of tumours of the CNS that are of relevance to the paediatric neuroradiologist when it comes to day-to-day reporting.